THE EFFECT OF VISUAL MEDIA ON STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 SIBABANGUN 2019/2020 ACADEMIC YEAR - Lidi ani (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of this research are to know: 1) The application of Visual Media on Students’ Reading Comprehension of Narrative Text 2) The Students’ Reading Comprehension of Narrative Text before and after using Visual Media 3) Whether there is any significant effect of Visual Media on Students’ Reading Comprehension of Narrative Text at the eleventh grade of SMA Negeri 1 Sibabangun. The population of this research is all of the eleventh grade of SMA Negeri 1 Sibabangun which consist of 196 studens. Sample were 35 students which taken by purposive sampling. The research method that is experimental method. Technique collecting data the writer used observation sheet and test. The result of the application of Visual Media was 3.7 categorized “Very good”. Before using Visual Media is 38.3 categorized “Fail”. Meanwhile, after using Visual Media is 68.2 categorized “Enough”. The result of data analysis show that ttest= 9.92 while ttable= 2.03. it means that ttestis higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of Visual Media on Students’ Reading Comprehension of Narrative Text at the eleventh grade of SMA Negeri 1 Sibabangun.